Underweight and Predictors Among Children Aged 6-59 Months in South Ethiopia - Temesgen Mohammed Toma; Temesgen Mohammed Toma; Kassahun Tamene Andargie; Rahel Abera Alula; Bahiru Mulatu Kebede; Kidus Temesgen; Tamirat Gezahegn Guyo (Frontiers Media S.A., 2024)
ObjectivesUnderweight remains the primary public health concern among under-five-year-old children in Ethiopia, despite numerous government-implemented nutrition-specific and sensitive interventions. Therefore, this study aimed to assess underweight and associated factors among children in South Ethiopia.MethodsBetween March and April 2021, 717 children in the South Ari district who were between the ages of 6 and 59 months participated in a cross-sectional study. To choose a sample of households containing a minimum of one child between the ages of 6 and 59 months, a multi-stage sampling procedure was used. Data were collected by interviewer-administered structured questionnaires from the mothers of the children. To determine the factors associated with being underweight, a binary logistic regression analysis was built. All variables with a p-value <0.25 in the bivariable analysis were entered into a multivariable logistic regression analysis. To assess the strength of the association, an adjusted odds ratio (AOR) with a 95% confidence interval was used. With a p-value below 0.05, statistical significance was declared.ResultsThe prevalence of underweight was determined to be 29.7% (95% CI: 26.5%, 33.2%). Child age 6-23 months [adjusted odds ratio (AOR) = 0.28; 95% confidence interval (CI): 0.18, 0.44], food insecurity (AOR = 1.48; 95% CI: 1.04, 2.10), sub-optimal child dietary diversity (AOR = 1.44; 95% CI: 1.01, 2.03), birth interval <24 months (AOR = 2.49; 95% CI: 1.75, 3.54), and common childhood illness (AOR = 2.21; 95% CI: 1.52, 3.21) were associated with being underweight.ConclusionUnderweight among children is predicted by household food insecurity, suboptimal dietary diversity, and common childhood illnesses, necessitating further efforts to improve food security and manage common illnesses.